Comparison of the association of risperidone and quetiapine with deteriorating performance in walking and dressing in subjects with Parkinson's disease: a retrospective cohort study using administrative claims data. (September 2019) - Iketani, Ryo; Imai, Shinobu; Horiguchi, Hiromasa; Furushima, Daisuke; Fushimi, Kiyohide; Yamada, Hiroshi
Abstract : This retrospective cohort study was performed to investigate the association between risperidone and deteriorating performance in walking and dressing in subjects with Parkinson's disease using the Japanese Diagnosis Procedure Combination data. These data include inpatient claims including information from the time of admission to discharge from 89 acute phase National Hospitals in Japan. The data were evaluated by implementing the inverse probability of treatment weighting, using propensity scores estimated from the clinical characteristics of subjects prescribed risperidone or quetiapine. The generalized estimation equation was used to estimate the adjusted risk ratios (aRRs) and 95% confidence intervals (CIs). In total, 304 subjects were eligible for participation, and were hospitalized between April 2012 and March 2017 (108 and 196 for risperidone and quetiapine groups, respectively). The performance of walking deteriorated at discharge, with 22.2% and 10.2% recorded at admission for the risperidone and quetiapine groups (aRR, 1.7; 95% CI, 0.9 to 3.4), respectively. The performance of dressing also deteriorated: 24.1% and 10.7% in the risperidone and quetiapine groups (aRR, 1.9; 95% CI, 1.04 to 3.7), respectively. These results suggest an association between risperidone and deteriorating performance in dressing in subjects with Parkinson's disease in comparison with quetiapine. Abstract : Supplemental Digital Content is available in the text.